Ultrastructure of Haemocytes Present during Flight Muscle Differentiation of Melipona quadrifasciata anthidioides, Lepidoptera (Hymenoptera, Apidae) - Da Cruz-landim, Carminda [UNESP] (My University, 1996)
The present work deals with the ultrastructure of the haemocytes present in the dorsal thoracic region of larvae and pre-pupae of Melipona quadrifasciata anthidioides. This is a region of intense muscular differentiation in this phase of life of the insect. Only plasmatocytes, granulocytes, and adipohaemocytes were found in this area, all showing signs of being intermediate forms.
Keywords: Haemocytes; Larvae; Pre-pupae; Stingless bee; Ultrastructure